2015
DOI: 10.3168/jds.2015-9645
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and physiological changes around estrus events identified using multiple automated monitoring technologies

Abstract: to explore the application of machine learning techniques to automatically collected data. Activity 4 level, lying bouts, lying time, rumination time, feeding time, and reticulorumen temperature 5showed differences between periods of estrus and non-estrus, but ear surface temperature did not. 6Additionally, applying machine learning techniques to automatically collected technology data 7shows potential for estrus detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 40 publications
1
62
3
1
Order By: Relevance
“…Furthermore, there can be substantial differences between rumination times estimated with acoustic neck tags versus accelerometer ear tags. In a study that used both types of sensors, Dolecheck et al (2015) reported that rumination times from Hi-Tag neck sensors were on average 39% greater than those from CowManager ear tag sensors (551 vs. 396 min/d, n = 18 cows). As mean rumination time in dairy cows is about 435 min/d (Table 1), it is not clear which sensor best represented actual rumination time.…”
Section: Measuring Chewing Timementioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, there can be substantial differences between rumination times estimated with acoustic neck tags versus accelerometer ear tags. In a study that used both types of sensors, Dolecheck et al (2015) reported that rumination times from Hi-Tag neck sensors were on average 39% greater than those from CowManager ear tag sensors (551 vs. 396 min/d, n = 18 cows). As mean rumination time in dairy cows is about 435 min/d (Table 1), it is not clear which sensor best represented actual rumination time.…”
Section: Measuring Chewing Timementioning
confidence: 98%
“…Greatest cow activity and lowest rumination time occurred between 0200 and 0800 h and 0400 and 1000 h on the day of estrus, respectively. In a study of 32 Holstein cows, several different automated monitoring technologies were used to monitor chewing activity, temperature, and activity before and during estrus (Dolecheck et al, 2015). Eighteen cows displayed estrus (standing to be mounted) during the study.…”
Section: Estrus Detectionmentioning
confidence: 99%
“…Some currently available accelerometers are equipped with a thermometer. Dolecheck et al 46 used CowManager SensOor and detected a significant increase in ear temperature during estrus, but their readings were not consistent. Moreover, the authors emphasized that the temperature of the ear to a large extent depends on external factors, and readings from the SensOor system cannot be used for the detection of estrus.…”
Section: Estrus Detectionmentioning
confidence: 98%
“…Some currently available accelerometers are equipped with a thermometer. Dolecheck et al . used CowManager SensOor and detected a significant increase in ear temperature during estrus, but their readings were not consistent.…”
Section: Estrus Detectionmentioning
confidence: 99%
“…Both mentioned sensor techniques measure the decreasing rumination time during estrus compared with nonestrus in study published by Dolecheck et al (2015). The percent change in rumination time between nonestrus and estrus for the CowManager SensOor and the HR Tag were -43.8 and -37.9 %, respectively.…”
Section: Feeding and Rumination Timementioning
confidence: 98%